STRATEGI GURU DALAM PENERAPAN PROFIL PELAJAR RAHMATAN LIL‘ALAMIN (P2RA) TERHADAP PENGUATAN KARAKTER KETELADANAN (QUDWAH) DI MI AL-AWWAL DAN MIN 2 PALEMBANG - Lailatul Mukjizat; Ahmad Syarifuddin; Amir Hamzah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the teacher's strategy in implementing P2RA towards strengthening exemplary character (qudwah) at MI Al-Awwal and MIN 2 Palembang, to determine the results of teacher strategies in implementing P2RA towards strengthening exemplary character (qudwah) at MI Al-Awwal and MIN 2 Palembang, and to determine the inhibiting and supporting factors for teachers in implementing P2RA towards strengthening exemplary character (qudwah) at MI Al-Awwal and MIN 2 Palembang. The method used in this study is descriptive qualitative. Based on the research results found, the strategies used by teachers in implementing P2RA to strengthen the exemplary character of students are 1) integrating P2RA values ​​​​in the learning process. 2) Being a good role model for students. 3) Through routine religious activities held at the madrasah. The impact of the strategy used by teachers in implementing P2RA to strengthen the exemplary character of students, namely, can hone the interests and talents of students, increase insight, and improve student creativity and student morals to be better. The supporting factors in the strategy used by teachers in implementing P2RA to strengthen the exemplary character of students are: 1) Teacher competence in implementing P2RA during the learning process. 2) Teacher exemplary behavior as a role model for students. 3) Routine religious activities carried out at the madrasah. The obstacles found in the study were the lack of teacher understanding regarding the implementation of P2RA and factors from the environment outside the madrasah.